Construction of Education Based on Religious Moderation: Role of Islamic Education Leadership in Promoting Tolerance and Social Harmony - Wibowo, Adi; Roqib, Moh.; Subur, Subur; Aulia Kumala, Shofa (PT. Riset Press International, 2024)
This research focuses on the implementation of religious moderation-based education at An-Nawawi Berjan Purworejo Islamic Boarding School, with an emphasis on the role of Islamic education leadership, especially KH Ahmad Chalwani. In the era of globalisation and the complexity of multicultural society, Islamic educational institutions have an important role in building attitudes of tolerance and social harmony. The religious moderation approach is recognised as effective in developing inclusiveness, tolerance and respect for religious diversity. This research used a qualitative approach with a case study design, involving the leadership, teachers, and students of An-Nawawi Berjan Islamic Boarding School in Purworejo. Data were collected through interviews, direct observation, and document analysis, then analysed thematically to identify key patterns. The findings show successful integration of the principles of religious moderation in the curriculum, school policies, and daily teaching practices, which enhances students' understanding and participation in appreciating religious diversity. Discussion of the findings highlights the importance of religious moderation-based education in responding to the challenge of religious extremism. The contribution of Pondok Pesantren An-Nawawi Berjan Purworejo in promoting inclusive and tolerant education sets an example for other educational institutions in building a harmonious society amid increasingly complex religious diversity. This research confirms the relevance and essentiality of religious moderation-based education in the context of Islamic education, as well as providing practical guidance for stakeholders in strengthening the values of moderation, tolerance and diversity in education and society.